Gerardo Mello Mourão e a gênese épica de Invenção do Mar - Silva, Edson Oliveira da (2010)
Observation, memory and imagination are considered the premise of epic poems since Aristotle. However, the intersection of these three structures that permeated Homer, Virgil and Camões’ poems has allowed some space, in contemporaneity, to the emergence of a phenomenon that significantly restructures the epic poetry as a conceptual object: the articulation of the speaker. Thus, The Invention of the Sea, written by Geraldo Mello Mourão, a poet from Ceará, is a kind of invention, as it is suggested by the title. This work deconstructs the frontiers that separate the literary genres and creates another type of canto, which is able to mould the heart’s voice on the great deeds involved in the discovery and colonization of Brazil since the 16th Century and the following centuries. In this perspective, this thesis aims at identifying and analyzing the use and the recreation of the epic genre in Brazilian contemporary poetry in order to understand the aesthetic and thematic structure in The Invention of the Sea, to discuss the articulation of the binomial literature-history and to understand the interstices of time and space that determine the ethnic and cultural construction of Brazilian people.